2020
DOI: 10.3920/jiff2019.0020
|View full text |Cite
|
Sign up to set email alerts
|

Research and industrialisation ofHermetia illucens L. in China

Abstract: The larvae of the black soldier fly (BSF), Hermetia illucens L., are commonly associated with decaying organic wastes. Over the past 15 years, investigators in China have conducted extensive research exploring the use of BSF larvae to recycle organic materials as a means to protect the environment, while producing products of value, such as protein and bioenergy. Initial efforts were based on a BSF strain from the USA. However, since then, H. illucens strains from specimens collected in Hubei and Guangdong Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…This of course fits well in the policy of a circular economy now adopted as a sustainable development strategy in European and Chinese policy making (Ranta et al, 2018). Biodegradation can be the purpose, such as in China where manure and catering waste are targeted (Zhang et al, 2020). However, bioconversion or biotransformation are more often envisioned.…”
Section: Black Soldier Flysupporting
confidence: 63%
“…This of course fits well in the policy of a circular economy now adopted as a sustainable development strategy in European and Chinese policy making (Ranta et al, 2018). Biodegradation can be the purpose, such as in China where manure and catering waste are targeted (Zhang et al, 2020). However, bioconversion or biotransformation are more often envisioned.…”
Section: Black Soldier Flysupporting
confidence: 63%
“…After UV induction, the increase in organic acids indicates that BSF can digest cellulose from food waste. Zhan et al reported the BSF genome had experienced considerable development in functional modules that improved BSF’s adaptation to adverse environments, including immune system elements [ 25 ]. The immune system of BSF could be adapted to alleviate pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini dikarenakan residu hasil biokonversi larva BSF belum melalui proses pengomposan yang sempurna sebelum dilakukan analisis uji kandungan. Berdasarkan prosedur perusahaan, sebelum residu hasil konversi digunakan harus melalui tahap didiamkan selama beberapa hari karena residu biokonversi belum stabil (Liu et al, 2019;Zhang et al, 2020).…”
Section: Kualitas Kompos Hasil Biokonversiunclassified